2006
DOI: 10.2310/7070.2006.0066
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging Findings in Sudden Sensorineural Hearing Loss

Abstract: Objective: To investigate the role of magnetic resonance imaging (MRI) in the diagnosis of sudden sensorineural hearing toss (SSNHL).Methods: Fifty-four consecutive patients affected by SSNHL were investigated using brain MRI. MRI was performed with an eightchannel phased-array head coil to study the entire audiovestibular pathway and the whole brain. The protocol study consisted of a highresolution study of the temporal bone, internal auditory canal (lACI, cerebellopontine angle (CPA). and brainstem combining… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
3
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 0 publications
4
40
3
3
Order By: Relevance
“…Of the 13 3D-FLAIR-positive patients, 7 (54%) showed multiple subsites of high-intensity signal, while 6 patients (46%) had only 1 subsite of hypersignal (5 cases in the cochlea only, and 1 case in the cochlear nerve) (Figure 1). In 3 patients (23%), there was high-intensity signal in T1-weighted MRI images; in 3 patients (23%), a highintensity signal only in the 3D-FLAIR sequence; and in 7 From the combined analyses of T1 and FLAIR sequences, and from the findings of other researchers, 7,9,12 we identified 3 possible radiologic patterns:…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the 13 3D-FLAIR-positive patients, 7 (54%) showed multiple subsites of high-intensity signal, while 6 patients (46%) had only 1 subsite of hypersignal (5 cases in the cochlea only, and 1 case in the cochlear nerve) (Figure 1). In 3 patients (23%), there was high-intensity signal in T1-weighted MRI images; in 3 patients (23%), a highintensity signal only in the 3D-FLAIR sequence; and in 7 From the combined analyses of T1 and FLAIR sequences, and from the findings of other researchers, 7,9,12 we identified 3 possible radiologic patterns:…”
Section: Resultsmentioning
confidence: 99%
“…Thus, 3D-FLAIR hyperintensity indicates the modification of the inner ear protein composition that can be ascribed to a minor hemorrhage or to an acute inflammatory process. 9 Also, 3D-FLAIR imaging can detect the BLB breakdown as the enhancement of the endolabyrinthic fluid signal and/or nerve signal after gadolinium injection owing to its high sensitivity to magnetic susceptibility. 7 In our experience 3D-FLAIR imaging is more sensitive to hematolabyrinthic and hematonervous barrier breakdown than T1 imaging, with fat suppression increasing the diagnosis accuracy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In one study of patients with SHL, 57% of the MRI studies revealed some abnormality, but only 20% of these findings were directly related to the hearing loss. 113 In another study, the overall rate of abnormal findings was 34.5%, with 36% of these directly related to the hearing loss. 112 In general, the rate of incidental findings in patients with audiovestibular symptoms is significant (47.5%), but only a small fraction of these (2.5%) required additional referral or investigation.…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%
“…The overall rate of pathogenic MRI abnormalities directly related to the SSNHL ranges from 7% to 13.75%. 60,98,[111][112][113] Therefore, MRI has the highest yield of any diagnostic test in the setting of SSNHL.…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%